2022
DOI: 10.21511/im.18(4).2022.13
|View full text |Cite
|
Sign up to set email alerts
|

What causes social media users to engage and mimic virtual influencers? The role of self-congruity

Abstract: Influencer marketing has been widely utilized in marketing communication. With the growing interest in virtual influencers, this study aims to investigate why social media users would interact with virtual influencers. The research model was developed based on the self-congruity theory. The data were obtained by questionnaires distributed to social media users using judgmental sampling (respondents were above 18 years old and actively used Instagram within the past six months). The questionnaire was posted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Moreover, Vis open new channels for consumer interaction through identity formation, autonomy and diversification (Arsenyan and Mirowska, 2021). Consumers even copy Vis' behaviours, as they would do with colleagues' and friends' behaviours (Suprawan and Pojanavatee, 2022). In fact, recent research has demonstrated that people react emotionally, cognitively and behaviourally to virtual agents like they do to real people, as brain activation in areas related to emotional and interpersonal experiences is seen during both types of interactions (Arsenyan and Mirowska, 2021).…”
Section: Millennials and Generation Z Consumer Reactions To Virtual I...mentioning
confidence: 99%
“…Moreover, Vis open new channels for consumer interaction through identity formation, autonomy and diversification (Arsenyan and Mirowska, 2021). Consumers even copy Vis' behaviours, as they would do with colleagues' and friends' behaviours (Suprawan and Pojanavatee, 2022). In fact, recent research has demonstrated that people react emotionally, cognitively and behaviourally to virtual agents like they do to real people, as brain activation in areas related to emotional and interpersonal experiences is seen during both types of interactions (Arsenyan and Mirowska, 2021).…”
Section: Millennials and Generation Z Consumer Reactions To Virtual I...mentioning
confidence: 99%
“…In the early stages of the design process, a co‐creative and participatory approach can offer a holistic view of what virtual ambassadors should look like and the benefits they can bring to the community. Suprawan and Pojanavatee (2022) investigated why SM users would interact with VIs. The researchers highlighted value homophily as the most important factor explaining why consumers respond to a VI when used as a message source in marketing communications.…”
Section: Future Research Agendamentioning
confidence: 99%